A Solution to the Systemic Issues with the Australian Retirement System. Issue 2 (18th November 2020) - Evans, John R.; Razeed, Abdul
Abstract : The Australian retirement system is likely to produce variable outcomes for retirees, with a high probability of delivering retirement standards of living below acceptable levels, and due to wage offsets, pre‐retirement standards of living could fall below acceptable levels if contributions were increased. To overcome the shortcomings, we consider the effect of introducing a fully funded Age Pension to replace the Superannuation Guarantee Levy (SGL) component of the retirement system. The results indicate the alternative fully funded Age Pension would deliver more reliable results for most retirees but with possible increased net costs to Government of the Age Pension.